Pengaruh Influencer Dan Endorsement Terhadap Purchase Intension Produk Erigo Fashion Pada Media Sosial Instagram - Akhmad Fadhili; Rois Arifin; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the simultaneous and partial influence of Influencers and Endorsements on Purchase Intention of Erigo Fashion Products on Instagram Social Media. This type of research is explanatory. The data collection technique uses a questionnaire through the Googlee Form. A sample of 154 respondents who have purchased Erigo fashion through Instagram in the last 3 months. Data analysis using Descriptive Statistics and Multiple Linear Regression. The results of the study show that influencers and endorsements simultaneously have a significant influence on Erigo Fashion's Purchase Intention on Instagram. This means that every increase in Influencer and Endorsement will be accompanied by an increase in Purchase Intention. Influencers have a significant influence on Purchase Intention, this means that an increase in the number of followers who like, the uniqueness of content about fashion, will increase Purchase Intention. Endorsement has a significant influence on Purchase Intention. This means that increasing the credibility, expertise and ability of Celebrity endorsers will increase Purchase Intention. Keywords: Influencer,  Endorsement ,  Purchase Intension